Current perspectives in Bietti crystalline dystrophy - García-García, GP (Clin Ophthalmol, 2019)
Bietti crystalline dystrophy (BCD) is a rare-inherited disease caused by mutations in the CYP4V2 gene and characterized by the presence of multiple shimmering yellow-white deposits in the posterior pole of the retina in association with atrophy of the retinal pigment epithelium (RPE) and chorioretinal atrophy. The additional presence of glittering dots located at the corneal limbus is also a frequent finding. The CYP4V2 protein belongs to the cytochrome P450 subfamily 4 and is mainly expressed in the retina and the RPE and less expressed in the cornea. The disease has its metabolic origin in the diminished transformation of fatty acid substrates into n-3 polyunsaturated fatty acids due to a dysregulation of the lipid metabolism. In this review, we provide updated insights on clinical and molecular characteristics of BCD including underlying mechanisms of BCD, genetic diagnosis, progress in the identification of causative genetic and epigenetic factors, available techniques of exploration and development of novel therapies. This information will help clinicians to improve accuracy of BCD diagnosis, providing the patient reliable information regarding prognosis and clinical prediction of the disease course.